Effects of Dissolved Oxygen and Hypoxia on Catch Rates of Nearshore Groundfishes in a Recreational Hook and Line Fishery - Leif K. Rasmuson; Alison D. Whitman; Brandy T. Cervantes; Jonathan P. Fram (Fisheries Oceanography, 2026)
Global climate change is intensifying ocean deoxygenation, particularly in eastern boundary current systems such as the California Current. This study investigates the impact of hypoxic events on a nearshore, multispecies recreational groundfish fishery along the Oregon coast. Using dissolved oxygen (DO) data from the National Science Foundation's Ocean Observatories Initiative (OOI) Oregon Inshore Mooring (2018–2022, excluding 2020) and trip‐level recreational fishery catch data from the Oregon Department of Fish and Wildlife, we modeled catch‐per‐unit‐effort (CPUE) and species encounter rates as functions of DO and regulatory bag limits. Of the 709 days analyzed, 36.8% were characterized as hypoxic (DO

Routine large-scale movements of the yelloweye rockfish (Sebastes ruberrimus) - Leif K. Rasmuson; Matthew T. O. Blume; Kelly A. Lawrence; Bruce M. Laughlin; Christopher A. Edwards; Mark R. Terwilliger; A. Camille Ayrea; Alexandra G. McInturf; Bryan J. Legare; Taylor K. Chapple (Frontiers in Marine Science, 2025)
Of the seven species of Pacific rockfish declared overfished in the California Current in 2008, yelloweye rockfish ( Sebastes ruberrimus ) is the only remaining overfished rockfish species. Part of the original rebuilding plan included designation of a yelloweye rockfish conservation area, a rocky reef closed off the Central Coast of Oregon that is closed to bottom fishing. The yelloweye rockfish conservation area’s ability to help rebuild the population, is predicated on the theory that demersal rockfishes are relatively sedentary. However, in the years since being declared overfished, acoustic tagging studies suggested yelloweye rockfish did not remain in the yelloweye rockfish conservation area. However, where they went remained a mystery. In this paper we describe the use of pop-off satellite tags to conduct a mark-recapture study of 11 yelloweye rockfish tagged within the Stonewall Bank Yelloweye Rockfish Conservation Area. We used back-in-time particle tracking coupled with an ocean circulation model in an attempt to increase the precision in the location at which each tag shed off the fish, and further validated that location by associating it to the underlying seafloor habitat type. Ten out of eleven tags were shed from the fish while it was outside the Stonewall Bank Yelloweye Rockfish Conservation Area’s boundary. While most fish remained within 50 km of the Stonewall Bank Yelloweye Rockfish Conservation Area, one tagged fish swam to an offshore reef off Central Washington (~40 km from the shore). Backtracked locations were more likely over rock than the initial satellite transmission, indicating the method was effective at identifying tag shed locations. We found no relationship between days at large, fish sex or length and the distance between release site and shed location. Our work supports a growing body of work that suggests yelloweye rockfish have less site fidelity than previously hypothesized.

Habitat use and activity patterns of female Deacon Rockfish (Sebastes diaconus) at seasonal scales and in response to episodic hypoxia - Leif K. Rasmuson; Mathew T. O. Blume; Polly S. Rankin (Environmental Biology of Fishes, 2021)
We combined a high-resolution acoustic telemetry array with presence/absence receivers to conduct a preliminary study of the seasonal movements, activity patterns, and habitat associations of the newly described Deacon Rockfish ( Sebastes diaconus ) . Eleven mature female Deacon Rockfish were tagged and monitored during an 11-month period, at a nearshore rocky reef off Seal Rock, Oregon, USA, an area of recurring seasonal hypoxia (defined as dissolved oxygen concentration [DO] < 2 mg l −1 ). Two tags were detected leaving the study area by day 35, indicating predation or emigration. Three tags became inactive within the array, indicating tag loss or fish death. Six “resident” fish inhabited the array for 246–326 days. Resident fish exhibited high site fidelity, small home ranges (mean 95% KDE = 4907 m 2 ), and consistent activity patterns for the duration of the summertime high-resolution array (5 months), except during seasonal hypoxia. Resident fish were strongly diurnal in summer, with high levels of daytime activity above the bottom in relatively rugose habitat, followed by nighttime rest periods in deeper, less rugose habitat. During summertime hypoxia, resident fish exhibited less daytime activity during daytime hours with no rest periods at night, inhabited shallower water depths, and moved well away from their core activity areas on long, erratic forays. During the winter, diel patterns were less evident with higher activity levels at night (than in the summer) and lower activity levels in the day (than in the summer). We propose that some Deacon Rockfish continuously inhabit nearshore reefs throughout the year, but that daily/seasonal movement patterns, seasonally occurring hypoxia, and prey preferences for planktonic organisms influence relocation.

Influence of the Seasonal Thermocline on the Vertical Distribution of Larval Fish Assemblages Associated with Atlantic Bluefin Tuna Spawning Grounds - Itziar Alvarez; Leif K. Rasmuson; Trika Gerard; Raul Laiz-Carrion; Manuel Hidalgo; John T. Lamkin; Estrella Malca; Carmen Ferra; Asvin P. Torres; Diego Alvarez-Berastegui; Francisco Alemany; Jose M. Quintanilla; et al. (Oceans, 2021)
Temperature is often an important variable influencing the vertical position of fish larvae in the water column. The same species may show different vertical distributions in areas with a strong near-surface seasonal thermocline compared to isothermal near-surface regions. In areas with a strong surface thermocline, tuna larvae show a significant preference for the near-surface warmer layers. Little is known regarding larval tuna vertical distribution in isothermal waters and on the vertical distribution of the associated larval fish assemblages. We conducted vertical stratified sampling using the same methodology and fishing device (MOCNESS) in the two major spawning areas of Atlantic bluefin tuna (BFT): western Mediterranean Sea (MED), characterized by a surface thermocline, and the Gulf of Mexico (GOM) which lacks thermal stratification. Tuna larvae occupied the upper 30 m in both areas, but the average larval depth distribution was consistently deeper in the GOM. In the MED, vertical distribution of larval fish assemblages was explained by temperature, and species such as BFT, Thunnus alalunga, and Ceratoscopelus maderensis, among others, coexist above the thermocline and are separated from species such as Cyclothone braueri and Hygophum spp. (found below the thermocline). In the GOM, the environmental correlates of the vertical distribution of the larvae were salinity and fluorescence. Mesopelagic taxa such as Ceratoscopelus spp. and Cyclothone spp., among others, had a shallower average distribution than Lampanyctus spp., Hygophum spp., and Myctophum spp.

Characterizing larval swordfish habitat in the western tropical North Atlantic - Justin J. Suca; Leif K. Rasmuson; Estrella Malca; Trika Gerard; John T. Lamkin (Fisheries Oceanography, 2018)
Swordfish Xiphias gladius (Linnaeus, 1758) are a circumglobal pelagic fish targeted by multiple lucrative fisheries. Determining the distribution of swordfish larvae is important for indicating reproductive activity and understanding the early life history of swordfish. We identify and characterize larval swordfish distributions during peak swordfish spawning throughout the Gulf of Mexico and western Caribbean Sea with generalized additive models ( GAM s) using catches of swordfish larvae during ichthyoplankton surveys in April and May of 2010, 2011, and 2012. The best fit GAM , as determined by stepwise, backward Akaike Information Criterion selection, included both physiochemical (temperature at 5 m, sea surface height anomaly ( SSHA ), eddy kinetic energy ( EKE )), temporal (lunar illumination, hour of sampling) and spatial (location) variables, while near surface chlorophyll a concentration residuals remained as a random effect. The highest probability of larval swordfish catch occurred at sub‐surface temperatures, SSHA , and EKE values indicative of boundary currents. Standard lengths of larvae were larger further downstream in the boundary currents, despite high variability in length with location due to multiple spawning locations of swordfish near these currents. Probability of larval swordfish catch also peaked during the crescent and gibbous moons, indicating a lunar periodicity to swordfish spawning. These results suggest that swordfish may spawn during select moon phases near boundary currents that transport their larvae to larval and juvenile habitat including the northern Gulf of Mexico and coastal waters of the southeast United States.

Fruits and vegetables consumption and the risk of histological subtypes of lung cancer in the European Prospective Investigation into Cancer and Nutrition (EPIC) - F. L. Büchner; H. B. Bueno-de-Mesquita; J. Linseisen; H. C. Boshuizen; L. A. L. M. Kiemeney; M. M. Ros; K. Overvad; L. Hansen; A. Tjonneland; O. Raaschou-Nielsen; F. Clavel-Chapelon; M.-C. Boutron-Ruault; et al. (Cancer Causes & Control, 2010)